Energy and Exergy Analysis of Single Effect Water-LiBr Vapour Absorption Refrigeration System - Sitotaw, Natnale (International Journal of Advanced Science Computing and Engineering, 2022)
Vapor absorption refrigeration system (VARS) is one of the emerging technology in thermal-driven refrigeration systems and has too many benefits in comparison with another cooling system as their performance is good and the cost is low. Different mathematical models of various complexities have been developed for performance analysis, optimization, and design of such systems. In this study energy and exergy of a single effect LiBr vapor absorption refrigeration system is analyzed with different mathematical model developed so far. The effect of varying the temperature for each component of the system on the coefficient of performance (COP) and exergetic efficiency (COPex) is briefly discussed. The results show that increasing generator temperature from 86oc to 102oc for constant refrigerant mass flow rate causes COP of the system to increase, due to the decrease in circulation ratio. In another case, increasing the evaporator temperature from 2oc to 14oc for a constant temperature input of the generator has a positive effect on both the first and second law efficiency of the VARS as the load on the generator decrease. From the result, it can also be concluded that increasing absorber temperature has a negative impact on both COP and exergetic efficiency of VARS.